A Study of Cosmetic Brand Name Translation in Iran - Khalilian, Zeinab; Rasekh, Abbas Eslami (Richtmann Publishing, 2012)
With the acceleration of economic globalization foreign products are being launched into the international market.Consequently, translating brand names successfully into other languages has never been more imperative and vital than today. Thetranslation of brand names is a kind of intercultural communication. Therefore, the translation of brand names is one of the mostchallenging activities every translator faces. While working on business literature, translation is especially complicated in cosmetic brandnames. Since advertising is important in these sort of products and we want to be certain that the product name will convey a friendlyimage in the foreign countries. This study, presenting an analysis of brand name translation, is based on Nida's functional equivalenceas its framework. It is tried to study the problems has been dealt with in the translation process. There are suggested ways to solvethem. And the results show that all names have been translated literally or transliterated and the denotative meaning of them employedwithout any attention to the connotation.